Construction of a new code for spectral amplitude coding in optical code-division multiple-access systems - Hasoon, Feras N.; Mohamad Khazani, Abdullah; Syed Alwee Aljunid, Syed Junid; Sahbudin, Shaari (Society of Photo-Optical Instrumentation Engineers (SPIE), 2009)
Link to publisher's homepage at http://spie.org/x867.xml